Methods of parallel vertical data processing in neural networks - Grytsyk, V.V.; Tsmots, I.G.; Skorokhoda, O.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
An operational basis of neural networks has been identified. The feasibility of development of parallel-vertical hardware neural networks has been substantiated. A parallel-vertical data processing method in neural elements (neural networks) that is oriented to the VLSI implementation and provides a reduction of the number of interface's pins, the bitness of interneuron connection, and equipment costs has been developed. The principles of the VLSI implementation of neural networks have been proposed.